Responding to the Call of Compromisso: Reflections on Research Ethics from the Ground of Capoeira Angola - Esther Viola Kurtz (Conversations Across the Field of Dance Studies)
This essay explores how call-and-response exchanges in Capoeira Angola both embody and generate ethical ways of being in the world. By bringing ethnographic specificity to a discussion of ethics, I ground the often-abstract nature of ethical thought in movement, sound, and lived experience. Drawing on my experiences of training with one capoeira group in Bahia, Brazil, I argue that when players enter capoeira’s ring of play, they also enter ethical relations with one another, which extend beyond moments of play into their lives. They call these ongoing responsibilities compromisso. Considering my roles as a guest, part-time student, and ethnographer, I ask what ought to comprise my compromisso with the group, and I reflect on the ways in which learning Capoeira Angola continues to influence how I think about research ethics.